Wireless Sensor Network over High Altitude Platform - Veronica Windha Mahyastuty; Iskandar Iskandar; Hendrawan Hendrawan; M. Sigit Arifianto (Universitas Ahmad Dahlan, 2018)
One of Machine Type Communication (MTC) applications is Wireless Sensor Network (WSN). WSN is an intelligent network application system to collect, integrate, and transmit data autonomously. Sensor nodes in WSN, communicate over short distance via a wireless medium and collaborate to accomplish a common task, such as enviroment monitoring, military surveillance and industrial process control. The constraining aspect of WSN usage is the limited power of each sensor node, so energy efficiency becomes an important issue in WSN. Routing is a function in WSN, which consumes a substantial amount of energy. One of the routing protocols that can increase the energy efficiency of WSN is Low Energy Adaptive Clustering Hierarchy (LEACH). In this paper, High Altitude Platform (HAP) is used to replace Base Station (BS) as sink node in WSN. HAP is designed at altitudes of 17, 20 and 22 km. Then WSN over HAP using the LEACH routing protocol evaluated its performance. Performance indicators that we evaluated are engergy consumption, number of dead nodes and total average packets which is sent to HAP. From a series of simulations conducted, the results obtained that the higher the laying of HAP, then the coverage area will be greater. So that the energy consumption will be smaller, the number of dead node less and the avarage of total packet delivered to the HAP will be greater.